2021
DOI: 10.1038/s41598-021-91454-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen suppressed tumor progression through the improvement of tumor hypoxia and induction of tumor apoptosis in A549-cell-transferred lung cancer

Abstract: Tumor cells have long been recognized as a relative contraindication to hyperbaric oxygen treatment (HBOT) since HBOT might enhance progressive cancer growth. However, in an oxygen deficit condition, tumor cells are more progressive and can be metastatic. HBOT increasing in oxygen partial pressure may benefit tumor suppression. In this study, we investigated the effects of HBOT on solid tumors, such as lung cancer. Non-small cell human lung carcinoma A549-cell-transferred severe combined immunodeficiency mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Thus, both the hyperoxia and pressure components of HBOT play an indispensable role in promoting angiogenesis. To date, numerous studies have reported the pro-angiogenesis effects of HBOT in different tissues with compromised blood perfusion such as skin [ [26] , [27] , [28] , [29] ], brain [ [30] , [31] , [32] ], penile [ 33 ], bone [ 34 ], and even tumor [ 35 , 36 ]. These results firmly establish the pro-angiogenesis effects of HBOT, implying its possible advantages in preventing age-related microcirculation impairments.…”
Section: The Mechanisms By Which Hbot Intervenes Agingmentioning
confidence: 99%
“…Thus, both the hyperoxia and pressure components of HBOT play an indispensable role in promoting angiogenesis. To date, numerous studies have reported the pro-angiogenesis effects of HBOT in different tissues with compromised blood perfusion such as skin [ [26] , [27] , [28] , [29] ], brain [ [30] , [31] , [32] ], penile [ 33 ], bone [ 34 ], and even tumor [ 35 , 36 ]. These results firmly establish the pro-angiogenesis effects of HBOT, implying its possible advantages in preventing age-related microcirculation impairments.…”
Section: The Mechanisms By Which Hbot Intervenes Agingmentioning
confidence: 99%
“…Their results revealed that HBOT improves tissue angiogenesis and tumor hypoxia and increases tumor apoptosis by modifying the tumor's hypoxic microenvironment. The treatment also suppressed tumor growth in murine xenograft tumor models (57). This was the first study to demonstrate that HBOT immediately downregulated endogenous p53 protein, which rebounded to baseline after 20 h of treatment.…”
Section: Chemoradiotherapymentioning
confidence: 65%
“…The anticancer effects of hyperoxia and its action mechanisms are mostly identified in mouse lung cancer (55,56). To detect the potential mechanism of HBOT in lung tumors, Chen et al (57) selected, as an in vivo model, non-small cell human lung carcinoma A549-cell-transferred severe-combined immunodeficiency mice (SCID). Their results revealed that HBOT improves tissue angiogenesis and tumor hypoxia and increases tumor apoptosis by modifying the tumor's hypoxic microenvironment.…”
Section: Chemoradiotherapymentioning
confidence: 99%
“…Another efficient method to increase tumor oxygenation is to provide a gas enriched in oxygen, for example 100% oxygen or carbogen (i.e., mixture of 95% O 2 and 5% CO 2 or 98% O 2 and 2% CO 2 ) (Siemann et al, 1977;Rojas et al, 1990;Falk et al, 1992;Grau et al, 1992;Horsman et al, 1994;Hoskin et al, 1997;Hill et al, 1998;Kaanders et al, 1998;Powell et al, 1999;Kaanders et al, 2002;Overgaard, 2007;Hoskin et al, 2009;Khan et al, 2009;Hoskin et al, 2010;Khan et al, 2010;Overgaard, 2011;Janssens et al, 2012;Thews and Vaupel, 2016;Song et al, 2021). Hyperbaric oxygen has also demonstrated a beneficial effect to reoxygenate tumors (Henk et al, 1977;Haffty et al, 1999;Becker et al, 2002;Thews and Vaupel, 2015;Chen et al, 2021). While breathing oxygen or carbogen is efficient in alleviating tumor hypoxia, some pharmacological approaches have led to a better response in sensitizing tumors to irradiation because they may act by several mechanisms including intrinsic radiosensitizing properties.…”
Section: Alleviation Of Tumor Hypoxia At the Time Of Radiation Therapymentioning
confidence: 99%